Strategi Dinas Kebudayaan Dan Pariwisata Provinsi Sumatera Selatan Dalam Mempromosikan Objek Wisata Melalui Media Instagram @pesonasriwijaya - Pratiwi, Diany Putri; Marleni, Marleni; Fadilla, Anissa Maharani; Austin, Trecy (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
The strategy of the South Sumatra Provincial Culture and Tourism Office in promoting Tourism Objects through Instagram media @pesonasriwijaya aims to describe the way of the promotion strategy of the South Sumatra Provincial Culture and Tourism Office on Instagram social media. This type of research uses qualitative methods using AISAS Theory (Attention, Interest, Search, Action and Share). The results of this study indicate that the strategy used by the South Sumatra Provincial Culture and Tourism Office in promoting tourist attractions through the sriwijaya charm Instagram media is through the messages they convey on the sriwijaya charm Instagram, then attracting audience interest through post content, utilizing Instagram features such as highlights and hashtags to make it easier for people to find out tourist attraction information, making persuasive invitation sentences in each post caption, and making posters and sharing travel testimonials with the public.